Sosialisasi Perhitungan TER PPh Pasal 21 di Lingkungan Kecamatan Simokerto Kota Surabaya (PP 58 Tahun 2023 dan PMK 168 Tahun 2023 ) - Adrianto Trimarjono; Wiwin Wahyuni; Lilik Mardiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Currently, one concrete manifestation of community participation in nation building is by paying taxes. Tax contributions in recent years have become increasingly significant and can be taken into account as the backbone of national financing sources in order to make national development programs a success that will increase economic growth. The number of taxpayers is also increasing from time to time as a reflection of increasing taxpayer awareness and compliance. MSMEs in Simokerto District, Surabaya, as part of the Taxpayers, we will accompany in realizing compliance as Taxpayers in the hope of knowing the latest regulations and calculation methods for withholding PPh Article 21 in the previous provisions, which have high complexity and calculation schemes that vary greatly. PPh Article 21 tax on individuals is very comparable to other withholding tax systems (for example: Final Income Tax, PPh Article 23), making it difficult for Taxpayers to fulfill their PPh Article 21 obligations. Government Regulation Number 58 of 2023 concerning Tax Withholding and Imposition Rates has been stipulated. Income Article 21 on Income in Connection with Work, Services or Activities of Individual Taxpayers (PP) which applies on January 1 2024